The Impact of Educandy Word Search Game on Enhancing Students’ Vocabulary Mastery: A Pre-Experimental Study in Eighth Grade at SMPN 5 Pontianak - Novia Ramadhanti; Rosnija, Eni; Rahmani , Eka Fajar (English Education:Journal of English Teaching and Research, 2024)
This study has objective to ascertain the effect of the word search game Educandy on students’ vocabulary mastery. This research utilized a pre-experimental design with three treatments as its methods. The research sample encompassed 31 students of VIII G at SMPN 5 Pontianak during the academic year of 2023/2024. The researcher used a test as an instrument and a measurement technique as a data collection method to complete this research. The results indicated that using the word search game Educandy enhanced students’ vocabulary mastery of learning vocabulary. According to the Mean score of the pre-test and post-test, alongside the t-test analysis, the research outcomes showed an enhancement in students’ advancement. The mean score obtained during the pre-test was 70.32, whereas the mean score during the post-test was 88.14. The calculated t-test value was 10,36, higher than the t-table value of 1.697 at a significance level of 0.05 and degree of freedom of 30. Moreover, the effect size was 1.761, which corresponds to a strong effect size with a range of effect size > 0.5. In brief, the results showed that using the word search game Educandy enhanced students’ vocabulary mastery.